2006
DOI: 10.1590/s1413-86702006000400005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of maternal group B streptococcal colonization and related risk factors in a Brazilian population

Abstract: The objective of this study was to determine the prevalence of maternal group B Streptococcal (GBS) colonization and compare risk factor data related to GBS colonization. A prospective surveillance study of 598 pregnant women was conducted in two socioeconomically diverse maternity hospitals in Ribeirão Preto, Brazil between June and October 1999. Swabs from the lower vagina were obtained between 35 and 37 weeks gestation and cultured on selective media. Risk factor data were obtained by patient interview and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
16
1
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 20 publications
9
16
1
9
Order By: Relevance
“…The detected prevalence of 17.3% is similar to a global prevalence rate of 17.9% determined in a recent meta-analysis [20], lower than rates found in Brazil (17.9%–25.6%) [8–10], but relatively high compared with rates reported in Peru (6%) [7], Argentina (7.6%) [21], and Mexico (4%–10%) [22, 23]. Previous smaller descriptive studies in Guatemala found GBS colonization rates as low as 2.5% among predominately native Mayan, rural populations [24] to 14.4% among predominately urban, nonindigenous populations [25].…”
Section: Discussionsupporting
confidence: 82%
“…The detected prevalence of 17.3% is similar to a global prevalence rate of 17.9% determined in a recent meta-analysis [20], lower than rates found in Brazil (17.9%–25.6%) [8–10], but relatively high compared with rates reported in Peru (6%) [7], Argentina (7.6%) [21], and Mexico (4%–10%) [22, 23]. Previous smaller descriptive studies in Guatemala found GBS colonization rates as low as 2.5% among predominately native Mayan, rural populations [24] to 14.4% among predominately urban, nonindigenous populations [25].…”
Section: Discussionsupporting
confidence: 82%
“…This percentage was similar to that reported previously [1]. In other studies conducted in our region, a wide range of between 3% and 21% has been reported [4]. Fifteen (16.7%) of the 90 pregnant women with one or more clinical risk factors for early‐onset GBS defined by the CDC were colonized by GBS; for the preterm birth group the prevalence was 23.9% (Table 2).…”
Section: Comparison Of Characteristics Between the Hospital Populatiosupporting
confidence: 88%
“…The carriage rate found by us was higher when compared with the results described in Santa Catarina (21.6%) (Pogere et al , 2005), Ribeirão Preto (17.9%) (Zusman et al , 2006) and São Luis (20.4%) (Costa et al , 2008) (Fisher’s Exact Test, p = 0.0192, p = 0.005, p = 0.0143, respectively). However, the present data were similar to those described by other authors in Brazil: Rio de Janeiro (26%) (Benchetrit et al , 1982) and Campinas (27.6%) (Nomura et al , 2006).…”
contrasting
confidence: 56%